2020
DOI: 10.1101/2020.03.19.20038703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential transcript usage unravels gene expression alterations in Alzheimer’s disease human brains

Abstract: Alzheimers disease (AD) is the leading cause of dementia in aging individuals. However pathophysiological processes involved in the brain are still poorly understood. Among numerous strategies, a comprehensive overview of gene expression alterations in the diseased brain has been proposed to help for a better understanding of the disease processes. In this work, we probed the differential expression of genes in different brain regions of healthy and AD adult subjects using data from three large studies: MAYO C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…For AD, major themes included vesicle-mediated transport in the synapse, regulation of catabolism, and chemical synaptic transmission, while other themes included organelle organization and macro-and autophagy cellular processes. These processes have been implicated by various AD snRNA-seq studies of DEGs as well (Mathys et al, 2019;Marques-Coelho et al, 2021;Grubman et al, 2019;Srinivasan et al, 2020). bMIND also identified notable enrichment of CTS-DEGs in astrocytes, highlighting gliogenesis, astrocyte differentiation/development, and glial cell proliferation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For AD, major themes included vesicle-mediated transport in the synapse, regulation of catabolism, and chemical synaptic transmission, while other themes included organelle organization and macro-and autophagy cellular processes. These processes have been implicated by various AD snRNA-seq studies of DEGs as well (Mathys et al, 2019;Marques-Coelho et al, 2021;Grubman et al, 2019;Srinivasan et al, 2020). bMIND also identified notable enrichment of CTS-DEGs in astrocytes, highlighting gliogenesis, astrocyte differentiation/development, and glial cell proliferation.…”
Section: Discussionmentioning
confidence: 83%
“…The different numbers of DEGs can be explained by sample size and brain region heterogeneity. At the bulk expression level, an existing study (Marques-Coelho et al, 2021) also found more DEGs in the temporal lobe (Mayo data and MSBB Brodmann areas 22 and 36) than in frontal lobe (ROSMAP data and MSBB Brodmann areas 10 and 44). When we contrasted the ExN-DEGs found from snRNA-seq (Mathys et al, 2019), we observed significant overlap with bMIND ExN-DEGs for both the Mayo and MSBB data (Fisher's exact test p-value = 3.9 × 10 −13 and 1.8 × 10 −5 , respectively).…”
Section: Cts Differential Expression Analysis Of Brain Tissue From Alzheimer's Disease Subjectsmentioning
confidence: 82%
“…Assignment of newly identified AD risk genes to specific cell classes of the adult brain was performed as previously described 52 . Briefly, middle temporal gyrus (MTG) single-nucleus transcriptomes (15,928 total nuclei derived from 8 human tissue donors ranging in age from 24-66 year), were used to annotate and select 6 main cell classes using S eurat 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell type expression. Assignment of newly identified AD risk genes to specific cell classes of the adult brain was performed as previously described 52 Table 23. PRS were calculated as previously described 34 .…”
Section: Definition Of Associated Loci a Region Of +/-500kb Was Defimentioning
confidence: 99%
“…The different numbers of DEGs can be explained by sample size and brain region heterogeneity. At the bulk expression level, an existing study (Coelho et al, 2020) also found more DEGs in the temporal lobe (Mayo data and MSBB Brodmann areas 22 and 36) than in frontal lobe (ROSMAP data and MSBB Brodmann areas 10 and 44). When we contrasted the ExN-DEGs found from snRNA-seq (Mathys et al, 2019), we observed significant overlap with bMIND ExN-DEGs for both the Mayo and MSBB data (Fisher's exact test p-value = 3.9 × 10 −13 and 1.8 × 10 −5 , respectively).…”
Section: Cts Differential Expression Analysis Of Brain Tissue From Almentioning
confidence: 82%